Misdiagnosis of a multi-organ involvement hematogenous disseminated tuberculosis as metastasis: a case report and literature review - Tian-Xing Hang; Gang Fang; Yan Huang; Chun-Mei Hu; Wei Chen (BMC, 2020)
Abstract Background Tuberculosis (TB) is a great mimicker and diagnostic chameleon, and prone to be diagnosed as malignancy. Even though many reports have described the differences between pulmonary TB and lung cancer, the atypical systemic hematogenous disseminated TB (HDTB) is very rare and more confusing in clinical practice. Case presentation A 73-year-old man, HIV-negative, was hospitalized to the local county hospital because of chest pain, low-grade fever, asthenia, anorexia and weight loss for the pasting two months. The CT findings of the two lungs showed multiple round or round-like nodules of different sizes, with clear boundaries and partial fusion. The level of serum CA19-9 was significantly higher than normal, and progressively increased. There were multiple enlarged lymph nodes in the neck, mediastinum, abdominal cavity and pelvic cavity. The symptoms were diagnosed as hematogenous spread of gastrointestinal tumor in the local county hospital. However, when transferred to our provincial hospital, through comprehensive dynamic analysis, this patient was diagnosed as atypical systemic HDTB, no cancer at all. Through routine anti-TB therapy for one year, the patient was recovered very well at the follow-up of half year after withdrawal. Conclusions In the past, most TB misdiagnosis cases involved in single organ and were finally confirmed through invasive examination. This case enriched clinical experiences in the diagnosis of atypical HDTB. We encouraged clinicians to establish a dynamic thinking for diagnosis and treatment and emphasized the value of biopsy and 18F-FDG-PET in distinguishing TB and cancer.